Trends in Systemic Antibiotic Therapy of Endodontic Infections: a Survey among Dental Practitioners in Lithuania - Alexander Mende; Tadas Venskutonis; Migle Mackeviciute (eJournal of Oral Maxillofacial Research)
Objectives: Prescription trends to certain antibiotic classes in Lithuania have been observed. Considering the potential contribution to antimicrobial resistance and the evidence of inappropriate prescriptions highlights, the periodical assessment of antibiotic consumption trends is required. The aim of this study was to assess prescription behaviours of Lithuanian general dental practitioners concerning the systemic antibiotic therapy of endodontic infections.